Adolescents’ Sexual Education: Parental Involvement in a Rural Area in Kwazulu-Natal, South Africa - Mavhandu-Mudzusi, Azwihangwisi Helen; Mhongo, Bongangani Glorious (Africa Journal of Nursing and Midwifery)
Parent-adolescent communication on sexuality is one of the key determinants of sexual and reproductive health outcomes of adolescents. Despite parent-adolescent communication on sexuality, statistics show an increase in the number of teenage pregnancies. This interpretative phenomenological analysis explored the perceptions of parents in a rural village in the Umzinyathi Health District in KwaZulu-Natal regarding the provision of sex education to adolescents. Ten parents of adolescent children were purposively selected to participate in the study, and data were collected using face-to-face, semi-structured interviews. Field notes were also taken to complement the audio recordings. Data were analysed thematically using the framework for interpretative phenomenological analysis. The results showed that rural parents face challenges in providing sex education to their teenagers. Sex education provided to adolescents is uncoordinated and haphazard. Parents have inadequate information and they are fearful and embarrassed to initiate sex talks with their teenagers. An age-appropriate, structured, formal, culture-sensitive, community-based sexual education programme aimed at empowering parents with knowledge and skills to provide contextual and age-relevant sex education to their teenage children is recommended.